2013
DOI: 10.1073/pnas.1300886110
|View full text |Cite
|
Sign up to set email alerts
|

Role for the kinase SGK1 in stress, depression, and glucocorticoid effects on hippocampal neurogenesis

Abstract: Stress and glucocorticoid hormones regulate hippocampal neurogenesis, but the molecular mechanisms mediating these effects are poorly understood. Here we identify the glucocorticoid receptor (GR) target gene, serum-and glucocorticoid-inducible kinase 1 (SGK1), as one such mechanism. Using a human hippocampal progenitor cell line, we found that a small molecule inhibitor for SGK1, GSK650394, counteracted the cortisol-induced reduction in neurogenesis. Moreover, gene expression and pathway analysis showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
222
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(256 citation statements)
references
References 36 publications
31
222
2
1
Order By: Relevance
“…Previous work has demonstrated that even after a prolonged period of severe stress -6 hrs of restraint water submersion -a similar two-fold increase in Sgk1 mRNA levels could be detected (Murata et al, 2005), suggesting that a sufficiently strong stressor can cause rapid and persistent activation of Sgk1 in the hippocampus. Our finding that stress-induced Sgk1 induction is independent of corticosterone and Crhr1 is in contrast with in vitro studies that report increased Sgk1 expression by corticosterone in cultured hippocampal progenitor cells (Anacker et al, 2013), as well as by Crh via Crhr1 signaling (Sheng et al, 2008). In vivo studies, however, have confirmed our observation that Sgk1 was not increased in the hippocampus after chronic nor acute high-dose corticosterone injections in rats and mice (Gray et al, 2013;Neeltje G van Gemert et al, 2006).…”
Section: Discussionsupporting
confidence: 67%
“…Previous work has demonstrated that even after a prolonged period of severe stress -6 hrs of restraint water submersion -a similar two-fold increase in Sgk1 mRNA levels could be detected (Murata et al, 2005), suggesting that a sufficiently strong stressor can cause rapid and persistent activation of Sgk1 in the hippocampus. Our finding that stress-induced Sgk1 induction is independent of corticosterone and Crhr1 is in contrast with in vitro studies that report increased Sgk1 expression by corticosterone in cultured hippocampal progenitor cells (Anacker et al, 2013), as well as by Crh via Crhr1 signaling (Sheng et al, 2008). In vivo studies, however, have confirmed our observation that Sgk1 was not increased in the hippocampus after chronic nor acute high-dose corticosterone injections in rats and mice (Gray et al, 2013;Neeltje G van Gemert et al, 2006).…”
Section: Discussionsupporting
confidence: 67%
“…We demonstrate that FKBP51 SUMOylation affects the expression of GILZ and SGK1, which are SUMOylation of FKBP51 regulates GR signaling M Antunica-Noguerol et al upregulated by GCs in the hippocampus. 33,34 In line with these results, our data show that GCs also induce the expression of SGK1 and GILZ in HT22 hippocampal neuronal cells. Moreover, we show that only SUMOylation-competent FKBP51 is involved in their regulation.…”
Section: Discussionsupporting
confidence: 88%
“…37 In particular, SGK1 was demonstrated to mediate the inhibitory effect of GCs on neuronal differentiation in human hippocampal progenitor cells. 33 In this respect, our data show that Dex inhibition of neurite outgrowth is regulated by FKBP51 in a SUMOylation-dependent manner. We show that expression of FKBP51 prevents both GR-mediated downregulation of neurite outgrowth together with the upregulation of SGK1; further and most importantly, that these two effects are dependent on SUMO conjugation to FKBP51.…”
Section: Discussionmentioning
confidence: 65%
“…Our observation that transient pharmacologic inhibition of GJIC is also sufficient to reduce NPSC proliferation (17) was recently confirmed in cultured embryonic stem cell-derived neural progenitors and in embryonic neural progenitors isolated from the cerebral cortex (34). Recent studies in human hippocampal neural progenitor cells indicate that the antiproliferative properties of GCs are dependent upon at least one genomic GR target gene, Sgk-1 (19). Consistent with these findings, Sgk-1 is also required for the antiproliferative effect of GCs in our NPSC cultures, since treatment with an SGK-1 inhibitor (GSK650394) blunts the growth-inhibitory affect of Dex ( Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Here we show that loss of the Dex-mediated antiproliferative response in NPSCs derived from Cav-1 knockout (KO) mice is associated with the alterations in Dex-induced expression of an established negative regulator of the cell cycle in NPSCs, the serum-and GC-induced kinase 1 gene, Sgk-1 (19). We also revealed more global effects of Cav-1 deletion on the GR transcriptome and uncovered a mechanism for Cav-1-mediated cross talk between rapid and genomic GR signaling that impacts site-specific GR phosphorylation and chromatin recruitment of GR.…”
mentioning
confidence: 98%